The SeaRAS AquaSense™ System: Real-Time Monitoring of H2S at Sub µg/L Levels in Recirculating Aquaculture Systems (RAS) - Lien, Eldar; Valsvik, Geir; Nordstrand, Jan Vidar; Martinez, Vincent; Rogne, Vegard; Hafsås, Ola; Queralt, Sara; Fathi, Behnood Sjåstad; Aga, Morten (Frontiers in Marine Science, 2022)
Hydrogen sulfide (H2S) is toxic to all species used in aquaculture. The extensive fish mortalities inflicted by H2S-poisoning can cause significant direct economic losses. Called the silent killer among scholars and fish farmers, H2S is highly soluble in aquatic environments and has significant damage potential; once detected, the time for mitigation actions is limited as fish stocks are rapidly impacted by the gas. The detection of H2S at low concentrations is challenging with the state-of-the-art sensors used today. Despite its significant damage potential, the industry has not been able to provide a reliable yet user-friendly system to address this. The aim of this paper is to provide a step forward in this direction by introducing a system for real-time monitoring of H2S at sub µg/L levels in RAS. The SeaRAS AquaSense System (AQS) utilizes real-time monitoring of H2S in parallel with other water quality parameters, such as CO2, O2, pH, and temperature, through a set of autonomous wireless-based sensor units installed in multiple locations in RAS. The system is calibrated and verified further by an autonomous calibration system where substrates of known values are brought to the sensor at a defined interval, offering the user data confidence that is exceptional and of high value. The H2S levels are measured in real-time at high-temporal resolution (down to 0.05 µg/L). By having units located in distinct locations in the water treatment loop, a true real-time monitoring of water treatment processes in RAS is given. Preliminary results provide new insights to the mechanisms behind H2S formation in operational RAS, and, more important, provide a basis for the development of risk-reducing actions and means for risk mitigation through degassing processes. By measuring real time simultaneously in multiple locations and in the exhaust of the degasser, a true mass balance of the system can be formulated by the given amount of feed, measured parameters by sensors and the known flow rate. By using the SeaRAS AquaSense System it is also possible to track the amount of H2S that leaks to the recirculating water per m2 of biofilm in RAS. This is a critical parameter and of high priority to be considered in the context of coping with the H2S-induced risks in RAS. The finding of this work highlights that the formation of toxic H2S is inevitable in RAS-process, ergo, the focus of the industry should instead go toward how to cope with it. In this regard, the SeaRAS AquaSense System provides a step forward towards a practical solution for managing H2S-poisoning risk in aquaculture. This work suggests a need for future research on determining acceptable limits for H2S in water quality context in RAS and investigating a new insight on interaction between H2S and other water quality parameters such as CO2.